Multilingual terminological dictionary in the context of a national terminology system formation - Verbinenko, Julia Ihorivna (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The problem of establishing a national system of terminology and related problems and methods of solution are considered in this article. The general requirements for multilingual terminological dictionary and specifications arising during the process of automation and digitizing were formulated. Experimental modeling was carried out on the body of the text of Ukrainian-Russian-English dictionary on welding. Interface of VLL "Welding" was presented and the basic tasks and system functionality were considered. Was unleashed the potential of the virtual laboratory and relevance of quick interaction between specialists of various fields.